Implementiation of ethics and management value in AnsarComp based on islamic perspective / Mohd Khairul Amri Mohd Kauji - Mohd Kauji, Mohd Khairul Amri (2018)
The literature suggests that ethics and management values are an important issue affecting organizational management and performance. This article aims to examine the ethics and values of Islamic management implemented at AnsarComp. This article also aims to examine the factors that influence the implementation of Islamic ethics and values in AnsarComp. This study was conducted using qualitative methods involving AnsarComp as a case study. Interview semi-structured was used as the primary data collection method, which was subsequently supported by researching the relevant documents. Employees and staff from Bahgian Human Resources AnsarComp were interviewed for information on the ethical implementation of Islamic management values at AnsarComp and the benefits gained from them. The results show that there are some ethical practices of Islamic work carried out by AnsarComp employees who work as worship to Allah SWT, discipline, trust, shura, fair, islah (continuous improvement) and earnest. The ethical and ethical implementation of effective Islamic work management also provides significant benefits to AnsarComp employees, to the AnsarComp organization itself and to the community. Among the benefits are the birth of employees who demonstrate high commitment to work, promotion opportunities, low-level employee retirement and loyal staff. Another benefit is that AnsarComp is actively involved in social responsibility, including the Welfare program under the AnsarCare Club. Ethical implementation and value management of Islam also help AnsarComp generate high business profits. This study demonstrates that with the cooperation of management and employees, work ethics and Islamic management values were successfully implemented in AnsarComp. The results or findings from this study can be used as guidance to managers in their efforts to effectively implement ethics and management of Islam.